(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
BIGALOG "The Rice N’ Egg" is a combination name of raw rice and raw egg that suits them perfectly to be easily recognized by the customers and stand out among other rice and egg businesses. The business intends to be customers’ preferred rice and egg store by providing them with the best quality goods and services at a reasonable price. The products that BIGALOG "The Rice n’ Egg" offers are raw rice and raw egg. Rice has different types of qualities: Jasmine Rice (Denurado), Coco Pandan, and Golden Star (Sinandomeng). The egg has two varieties: the regular egg and the salted egg. The target consumers are the retailers, sari-sari stores, food stall owners, tricycle drivers, carinderias, all pass-by commuters, online customers, and the residents of the 9 Kagawad Road Talanay Area A Barangay Batasan Hills, Quezon City. The researchers look forward to their business, BIGALOG "The Rice n’ Egg," managing, handling, and giving the satisfaction that every consumer deserves. They are also aspiring and aiming for the business’s overall success, especially during its operation.